CD8+ T-cell priming and boosting: More antigen-presenting DC, or more antigen per DC? - Schaft, Niels; Wellner, Verena; Wohn, Christian; Schuler, Gerold; Dörrie, Jan (Cancer Immunology, Immunotherapy, 2013)
RNA transfection is a standard method to load dendritic cells (DC) with antigen for therapeutic cancer vaccination. While electroporation yields high transfection efficiency and satisfying expression levels, lipofection results in only few cells expressing high amounts of antigen. We compared antigen loading of human monocyte-derived DC by MelanA RNA electroporation and lipofection. No differences in phenotype or migrational capacity were detected, but lipofected DC induced stronger cytokine secretion by antigen-specific T cells and were superior in priming and boosting of MelanA-specific CD8+ T cells. Interestingly, T cells stimulated with the differently transfected DC did not differ in their functional avidity. To determine whether the amount of antigen per cell is indeed responsible for the superiority of the lipofected DC, we increased the amount of MelanA RNA fivefold and mixed those DC with mock-electroporated ones to mimic the antigen distribution of lipofected cells. This significantly improved the stimulatory capacity, indicating that indeed the amount of antigen per cell seems to be the responsible feature for the observed superiority of lipofected DCs. These data suggest that a few DC that express high amounts of antigen are more immunogenic than many DC expressing lower amounts, although this needs to be tested in a two-armed immunogenicity trial. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Antigen presentation; Dendritic cells; Electroporation; Lipofection; T cells